(untitled) (Italian Journal of Public Health, 2006)
Increasing levels of genomic knowledge has led to awareness that new governance issues need to be taken into consideration. While some countries have created new statutory laws in the last 10 years, science supports the idea that genomic data should be treated like other medical data. In this article we discuss the three core models of governance in medical law on a conceptual level. The three models, the Medical, Public Health and Fundamental Rights Model stress different values, or in legal terms serve different principles. The Medical Model stands for expert knowledge and the standardisation of quality in healthcare. The Public Health Model fosters a social point of view as it advocates distribution justice in healthcare and an awareness of healthcare as a broader concept. The Fundamental Rights Model focuses on individual rights such as the right to privacy and autonomy. We argue that none of the models can be used in a purist fashion as governance in genomics should enable society and individuals to protect individual rights, to strive for a distribution justice and to ensure the quality of genomic services in one coherent process. Thus, genomic governance in genomics requires procedural law and a set of applicable principles. The principle which underlies all three models is the principle of medical beneficence. Therefore genomic governance should refer to it as a key principle when conflicting rights of individuals or communities need to be balanced.